Nationality, Ethnicity, and Solidarity: Respon Turki atas Perundingan Etnis Uighur - Moh. Fathoni Hakim; Denimah Denimah; M. Zulfikar Ramadhan; Devy Febian Arisandy Bahtiar; Feryan Airlangga; Stefano Jalu Sambowo Putra (Universitas Airlangga, 2021)
Uighur is an ethnic group which originally come from the Turkestan clan, which is predominantly found in Central and Western Asia Regions. As a minority within the People's Republic of China northwestern region, Its existence often sparks negative stigma from the China government. They are labelled as separatist groups. Large-scale demonstrations in 2009, which eventually led to riots between Uighur and Han Chinese population in Xinjiang, managed to worsen the situation. As a country that has primordial ties with the Uighur, Turkey has responded to the issue of discrimination that befell the Uighur. Therefore, this problem could bring tension to both Turkey and China. Utilizing the concept of bilateral diplomacy, this paper aims to examine the extent of the Turkish government's response to the issue of ethnic violence in Xinjiang. The findings show that the Uighur issue has always overshadowed Turkey-China bilateral relations ever since Its rise. Despite the disagreement, both have maintained a relatively good relation.